Screening for overweight and obesity utilizing bioelectrical impedance analysis in the health clinic setting - Kamaruzaman, Nor Azam; Zulkifli, Siti Dzulaikha; Said, Abdul Hadi; Pasi, Hafizah (Academy of Family Physicians of Malaysia (AFPM), 2024)
Introduction: The prevalence of overweight and obesity are increasing worldwide. Malaysia CPG had suggested the use of body composition assessment, measuring body fat percentage using bioelectrical impedance (BIA) to complement standard BMI and waist circumference. A clinic based body composition screening was conducted in conjunction with World Obesity Day 2024. The aim was to look at the prevalence of obesity and study the association between BMI and BF% among participants.